1991
DOI: 10.1111/j.1432-1033.1991.tb15724.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of hepatic mitochondrial 3‐hydroxy‐3‐methylglutaryl‐CoA synthase during the foetal/neonatal transition, suckling and weaning in the rat

Abstract: (1) We assayed active and total (i.e. active plus succinylated) 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) synthase in mitochondria isolated from foetal, neonatal, suckling or weaned rats.(2) HMG-CoA synthase was substantially succinylated and inactivated in mitochondria isolated from termfoetal, (1-h-old, 6-h-old, 1 -day-old) neonatal, suckling and high carbohydrate/low-fat (hc)-weaned rats. Succinylation of HMG-CoA synthase was very low in mitochondria isolated from the livers of foetal, 30-min-old neonatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 36 publications
(10 reference statements)
3
26
0
Order By: Relevance
“…The low HMG-CoA synthase activity did not result from a high succinylation state. Indeed, the succinylation state of pig mitochondria (5 %) was 4-fold lower than that of suckling rat liver mitochondria (Quant et al, 1991) that possess an active mitochondrial ketogenesis (Escriva et al, 1986). In fact, the low ketogenic capacity of newborn-pig liver mitochondria resulted from the extremely low amount of HMG-CoA synthase protein in newborn-or adult-pig liver mitochondria, as shown by Western-blot analysis ( Figure 2).…”
Section: Cpt and 11mentioning
confidence: 98%
See 1 more Smart Citation
“…The low HMG-CoA synthase activity did not result from a high succinylation state. Indeed, the succinylation state of pig mitochondria (5 %) was 4-fold lower than that of suckling rat liver mitochondria (Quant et al, 1991) that possess an active mitochondrial ketogenesis (Escriva et al, 1986). In fact, the low ketogenic capacity of newborn-pig liver mitochondria resulted from the extremely low amount of HMG-CoA synthase protein in newborn-or adult-pig liver mitochondria, as shown by Western-blot analysis ( Figure 2).…”
Section: Cpt and 11mentioning
confidence: 98%
“…Immune complexes were revealed as described previously (Quant et al, 1991). The polyclonal antibody was raised in the rabbit against the purified ox liver mitochondrial HMG-CoA synthase and shown to cross-react with the rat enzyme (Quant et al, 1991).…”
Section: Enzymes Of Ketone-body Synthesismentioning
confidence: 99%
“…We found that the expression of 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) synthase 2 (HMGCS2), the rate-limiting enzyme in ketogenesis in the liver (10,23,29), was significantly increased in the kidneys of db/db mice. We also measured the renal production of its major metabolite, ␤-hydroxybutyrate (␤-HB), in db/db mice and examined the effect of ␤-HB on TGF-␤ expression and collagen I production, as well as the epithelial-to-mesenchymal transition (EMT) in cultured rat proximal tubule cells.…”
mentioning
confidence: 97%
“…HMG-CoA synthase gene because rats weaned to a high-fat diet display elevated hepatic abundances of mt. HMG-CoA synthase mRNA [4,6], protein [4], and enzyme activity [5]. The brain, which requires a large input of fuel energy, is regarded as non-ketogenic [3] ; this is supported by the inability to detect, so far, mt.…”
Section: Introductionmentioning
confidence: 99%
“…HMG-CoA synthase mRNA [4] and mt. HMG-CoA synthase protein [4], which is proposed to be a major regulatory step in fatty acid-driven ketogenesis [5]. Changes in circulating fatty acid concentrations seem to regulate the expression of the mt.…”
Section: Introductionmentioning
confidence: 99%